The Geographies of Artists and Stall holders at Afrikaans Arts Festivals, South Africa - Stander, Jan Hendrik (Manna); Sandham, Luke Alan; Visser, Gustav (African journal of hospitality, tourism and leisure, 2021)
South African arts festivals have been the subject of considerable research, with a focus on the economics, attendee patterns and impacts on local communities. Importantly, numerous role-players (stall holders, artists, festival attendees, amongst others) contribute to the diversity, origin and character of these arts festivals. Despite this, little is known of their mobility, spatiality and geographies. To this end, artists and stall holders across five large Afrikaans Language Arts festivals were interviewed to establish their itineraries, travel behaviours, festival involvement and cultural expression. On this basis, this study hopes to enable a better understanding of the geographies of Afrikaans arts festivals. Results suggest that artists and stall holders contribute significantly to shaping the geographies of these arts festivals as they are the most mobile of all participants. Their mobility creates a shared or communal festival geography – albeit now severely disrupted by COVID-19 – across Afrikaans arts festival boundaries. Unfortunately, this shared geography may also undermine the local flavour, authenticity, and regional diversity of such arts festivals.